IMS, EMS, and the (n-1) problem - Claassen, Emil-Maria (Economic & Social Studies, 1989)
Three types of exchange rate regimes predominate the present international monetary system (IMS): the managed float by industrialised countries, a fixed but adjustable peg inside the European Monetary System (EMS), and in most cases a fixed peg by LDCs. Whatever the exchange rate arrangement is, all regimes share the so-called (n-l) problem which means that some minimum kind of co-operation is necessary with respect to the target of (n-l) independent exchange rates. Within the IMS, the problem is solved by the benign-neglect position of the USA with respect to their exchange rate. For the EMS, it could be solved by the Ecu (European currency unit) to the extent that it has reached the full status of a currency. However, for the moment, it seems to be solved by the German mark provided that Germany is only concerned with its exchange rate with respect to the dollar and remains indifferent with respect to the intra-EMS exchange rates. In this sense, one could identify the EMS with a German Monetary Area.
Keywords: European economics; European Monetary System; EMS